2019
DOI: 10.3390/su11195149
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Effectiveness of Prefabrication Incentive Policies in China

Abstract: Prefabrication is a technology that can reduce the material consumption during the construction process. Thus, it is regarded as a technology that be of assistance in the pursuit of sustainable development in the construction industry. In China, a series of policies has been formulated to promote the implementation of prefabrication; however, the effectiveness of these policies has not been investigated. The aim of this paper is to evaluate the effectiveness of the current prefabrication incentive policies in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Previous studies have concluded that the effectiveness of PBPs significantly affects the promotion and performance of PB (Mao et al, 2013;Park et al, 2011). However, the majority of the PB-related literature has neglected to investigate the formation and evolutionary processes of PBPs (Jiang et al, 2019). In this study, a bibliometric method was employed to identify the historical dynamics of China's PBP system.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have concluded that the effectiveness of PBPs significantly affects the promotion and performance of PB (Mao et al, 2013;Park et al, 2011). However, the majority of the PB-related literature has neglected to investigate the formation and evolutionary processes of PBPs (Jiang et al, 2019). In this study, a bibliometric method was employed to identify the historical dynamics of China's PBP system.…”
Section: Discussionmentioning
confidence: 99%
“…Without these PBPs, PB cannot be rapidly promoted due to the current path dependence of cast-in-situ construction technologies and the lack of market share (Mao et al, 2016). However, with the rapid promulgation of PBPs has come recognition of the complexity of policy design and implementation, which poses a significant challenge to policymakers who must develop effective approaches to enhance the efficiency of relevant policies (Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Z L Guo et al ( 2017 ) combined a rough set theory to redefine the factors that affect the risks associated with prefabricated housing (Guo et al 2017 ). Jiang (2019) selected four indicators, namely, the number of prefabricated component production enterprises, prefabricated building area, prefabricated building market size, and expected prefabricated building area ratio, to evaluate the effectiveness of a prefabricated building incentive policy (Jiang et al 2019b ). Pan (2020) combined the results of a questionnaire survey and those of related literature identified 10 influencing factors that hindered the implementation of prefabricated buildings in China, and used the ISM method to construct a multi-level hierarchical structure model of influencing factors.…”
Section: Literature Reviewmentioning
confidence: 99%